Reliability and agreement of three-dimensional/four-dimensional transperineal ultrasound in women with chronic pelvic pain - Maria Aparecida Mazzutti Verlangieri Carmo; Helmer Herren; Francisco J. C. Dos-Reis; Fabricio Da Silva Costa; Julio C. Rosa-; Antonio Alberto Nogueira; Omero Benedicto Poli-Neto (IMR Press, 2021)
Background: Chronic pelvic pain is a common complaint in the gynecological office. The association among anus levator muscle injury, CPP of unknown origin in parous women, and pelvic sensory symptoms have been demonstrated. The study's purpose is to assess the intrarater/interrater reliability and agreement of pelvic floor biometry and levator ani muscle injury evaluated using three-dimensional ultrasound in women with chronic pelvic pain. Methods: Two raters independently and blindly acquired three datasets of three-dimensional transperineal ultrasound volumes. The datasets were evaluated 60 days apart. To assess levator ani muscle injury, the hiatal area/diameter, levator ani muscle thickness, urethra-anus distance, and levator-urethra gap were measured. The intrarater reproducibility and interrater reproducibility were calculated. The concordance correlation coefficients and limits of agreement were analyzed in 147 three-dimensional ultrasound volumes obtained from 49 patients. Results: Levator ani muscle injury was detected in 10.2% (n = 5/49), with a good intrarater concordance correlation of >0.90 for anteroposterior diameter, hiatal area, levator-urethra gap, and urethra-anus distance. The hiatal transverse diameter and levator ani muscle thickness presented poor correlation, with limits of agreement of 28.2% and 29.7%, respectively. The levator-urethra gap also presented poor interrater concordance. Overall, the interrater evaluation had moderate to substantial concordance. Discussion: In the detection of levator ani muscle injury in parous women, the hiatal anteroposterior diameter, hiatal area, and urethra-anus distance can be reliably assessed using three-dimensional transperineal ultrasound of the pelvic floor. However, owing to poor reliability, the hiatal transverse diameter, levator ani muscle thickness, and levator ani muscle-urethra gap require more studies before they can be applied clinically.